The economic impact of the Budapest Airport on the local economy - Tamás Dusek; Miklós Lukovics; Patrick Bohl (European Regional Science Association (ERSA), 2011)
Airports have an unquestionably dominant role in the transport of the 21st century; air transport is the heart of the modern, globalised economy. Beyond this primary function, the international literature also emphasises the considerable economic and economy development effects of airports. The significant airports of the world not only facilitate the local economy but fundamentally determine that. The aim of the analysis is not only the study of the economic impact of the Budapest Ferihegy International Airport, but also examining the economic impact of the complex system of the companies operating at the airport and complementing each other. First of all, we discuss the methods and concepts to be applied in the analysis of the economic impact of the Budapest Airport. Although the methods and the terminology is fairly uniform in the course of the general review studies, the actual pieces of research can mean something different by the same concepts or they may examine the same thing with different concepts.
Keywords: 330